Pentosidine levels cannot be used to age a long-lived seabird. (3rd April 2019) - Labbé, Aurélie M. T.; Le Souëf, Anna T.; Dunlop, James N.; Calver, Michael; Shephard, Jill M.; van Keulen, Mike
ABSTRACT: Robust measurements of age are important for investigating ecological processes. In particular, seabirds, which form a major part of the coastal and marine ecosystems, may use and respond to their environment differently based on their age. This study aimed to determine whether pentosidine, a biological marker of age which was previously reliably used to age other avian species, could be used to age Bridled Terns ( Onychoprion anaethetus ) breeding on Penguin Island, Western Australia. It was found that patagial skin collagen-bound pentosidine cannot be used to determine the age of Bridled Terns because of low collagen levels in skin samples and that, overall, there was a low recapture rate of birds born on the island (less than 5% of the birds trapped in this study). Bridled Terns' diet and life at sea may explain their low skin collagen levels, but some molecular adaptations and antioxidants from their diet may help them resist oxidative challenge. Hence, methods for ageing birds based on collagen content in skin samples may not be uniform across species. Furthermore, low recapture rates in this colony may indicate high levels of dispersal or mortality, which warrant further investigation.